The Occupational Attainment of American Jewish Men in the Mid-19th Century - Barry R. Chiswick; RaeAnn H. Robinson (Global Labor Organization (GLO), 2023)
This paper is concerned with analyzing the occupational status of American Jewish men compared to other free men in the mid-19th century to help fill a gap in the literature. It does this by using the 1/100 microdata sample from the 1850 Census of Population, the first census to ask occupation. Two independent lists of surnames are used to identify men with a higher probability of being Jewish. The men identified as Jews had a higher probability of being professionals, managers, and craft workers, and were less likely to be in farm occupations or in operative jobs. Using the Duncan Socioeconomic Index (SEI), the Jewish men have a higher SEI overall. In the multiple regression analysis, it is found that among Jewish and other free men occupational status increases with age (up to about age 44 for all men), literacy, being married, being native born, living in the South, and living in an urban area. Controlling for a set of these variables, Jews have a significantly higher SEI, which is the equivalent of about half the size of the effect of being literate. This higher occupational status is consistent with patterns found elsewhere for American Jews throughout the 20th century.
Keywords: N31; J62; J15; 330; Jews; Occupational Status; Duncan Socioeconomic Index; 1850 Census of Population; Antebellum America; Labor Market Analysis; Human Capital